1985
DOI: 10.1177/0887302x8500400101
|View full text |Cite
|
Sign up to set email alerts
|

Retail Buyers of Apparel and Appliances: A Comparison

Abstract: The purpose of this study was to examine relationships among selected variables from a model of industrial buying behavior in the study of retail buying and to compare apparel and appliance buyers. One hundred-twenty apparel buyers and 126 appliance buyers responded to a mailed questionnaire. A factor analysis generated factors for Product Fashionability, Vendor, Negotiations, Supply, and Brand Name. Further analyses revealed that both groups of buyers relied on personal selling as an information source and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 12 publications
1
19
1
Order By: Relevance
“…apparel.' Francis and Brown (1985) compared apparel and appliance buyers' decision-making processes and found that &dquo;not all retail buyers are alike&dquo; (p. 7). This study extends that conclusion and further defines buyers in different apparel categories in small stores.…”
mentioning
confidence: 97%
“…apparel.' Francis and Brown (1985) compared apparel and appliance buyers' decision-making processes and found that &dquo;not all retail buyers are alike&dquo; (p. 7). This study extends that conclusion and further defines buyers in different apparel categories in small stores.…”
mentioning
confidence: 97%
“…Vendor judgments have been identified by researchers (Ettenson & Wagner, 1986;Francis & Brown, 1985;Hirschman, 1981;Hirschman & Mazursky, 1982;Kissel, 1985;Sheth, 1973). These studies reported that buyers view price, delivery, vendor reputation, steady source of supply, selling history, terms of sale, past experience with vendor, financial condition of vendor, return policy, and promotional incentives to be of major importance in determining the saleability of merchandise.…”
Section: Saleability Judgmentsmentioning
confidence: 93%
“…Brand name was one of the most often cited product variables used to determine merchandise saleability (Hirschman, 1981). Francis and Brown (1985) reported apparel buyers were the most concerned with product variables such as styling and quality when determining merchandise saleability.…”
Section: Saleability Judgmentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Supplier selection criteria have been the subject of investigation for more than four decades (Lin & Wu, 2011;Kim & Boo, 2010;Kahraman, Cebeci & Ulukan, 2003;Da Silva, Naude & Davies, 2001;Hansen, 2001;Pelligrini, & Zanderighi, 2001;Wilson, 1994;Fiorito, 1990;McLaughlin & Rao, 1989;Wagner, Ettenson & Parish, 1989;Francis &Brown, 1985-86 andNilsson, 1977). The supplier selection criteria consist of a list of criteria or factors that retailers generate whenever supplier selection decisions have to be made, as well as when determining which supplier purchases will be made (Braglia & Petroni, 2000).…”
Section: Supplier Selection Criteria Used By Craft Retailersmentioning
confidence: 99%